2015
DOI: 10.1016/j.jtumed.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of genome-wide association studies to identify novel genetic variants underlying the plasma lipoprotein metabolism as risk factors for CAD

Abstract: Coronary artery disease (CAD) is a major killer across the world. The pathogenesis of CAD is a construct of multiple predisposing elements, including environmental, health and genetic factors. Traditional risk factors for CAD include age, hypertension, diabetes, smoking, and dyslipidaemia. Optimizing the lipid levels to within the normal range significantly and drastically reduces the risk of coronary atherosclerosis. Genome-wide association studies (GWASs) promise to accurately identifying the variants that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…These factors act independently or in concert with each other to increase the risk of CAD. Controlling for the known risk factors of CAD, such as smoking, randomized clinical trials have shown that hypercholesterolaemia 2 is associated with an approximately 30–40% reduction in clinical events, such as myocardial infarction and subsequent death 3 . The other 40–60% of the risk of CAD is heritable according to epidemiological, twin and family studies.…”
Section: Introductionmentioning
confidence: 99%
“…These factors act independently or in concert with each other to increase the risk of CAD. Controlling for the known risk factors of CAD, such as smoking, randomized clinical trials have shown that hypercholesterolaemia 2 is associated with an approximately 30–40% reduction in clinical events, such as myocardial infarction and subsequent death 3 . The other 40–60% of the risk of CAD is heritable according to epidemiological, twin and family studies.…”
Section: Introductionmentioning
confidence: 99%